SORBENTS FOR EXTRACTION OF SPILLED FUEL-LUBRICATE MATERIALS - Mashinskaya, Natalya V.; Luganova, Tetyana O.; Pugachevskaya, Eugenya P. (Proceedings of National Aviation University (archive), 2009)
Properties of absorbents of biological structure have been researched in the work. Its main advantages in comparison with chemical and polymeric sorbents have been shown. The offered Canadian peat-moss can be used in Ukraine as sorbent for oil products spill liquidation.